Władysław Natanson - physicist and philosopher - Czapla, Krzysztof (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
Scientific works of Wladyslaw Natanson (1864-1937) are briefly reviewed, especially his achievements in the theory of irreversible processes and in the statistical theory of radiation. His philosophical and methodological views are also presented.